1985
DOI: 10.3758/bf03200028
|View full text |Cite
|
Sign up to set email alerts
|

Play soliciting behavior in prepubertal and postpubertal male rats

Abstract: Pre-and postpubertal play soliciting behavior was observed in intact males, castrate males, sham-operated males, and female controls. Although play soliciting decreased markedly with age in all groups, male treatment groups did not differ reliably on pre-or postpubertal tests. Males, however, engaged in reliably greater play soliciting than females on all measures in both preand postpubertal tests. These results suggest that the major decrease in social play associated with the attainment of sexual maturity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…These data agree with those in rats, for which prepubertal GNX also does not alter the decline in play [16,17]. Unlike in rats [18,19], however, prepubertal GNX increased levels of play in Siberian hamsters at P30 (P<0.004, main effect of GNX, ANOVA).…”
Section: Resultssupporting
confidence: 88%
“…These data agree with those in rats, for which prepubertal GNX also does not alter the decline in play [16,17]. Unlike in rats [18,19], however, prepubertal GNX increased levels of play in Siberian hamsters at P30 (P<0.004, main effect of GNX, ANOVA).…”
Section: Resultssupporting
confidence: 88%
“…The present findings also reveal that while males and females differ in the frequency of play (Thor & Holloway, 1985) in the age-related changes in the fighting tactics used during play fighting (Meaney & Stewart, 1981;Pellis & Pellis, 1990), and in the likelihood that their play fights will escalate into serious fights (Smith, Forgie & Pellis, 1998;Takahashi & Lore, 1983), both sexes become rougher in their play with age. These results are not consistent with the view that following puberty, females find male playmates less appealing because they play too roughly (e.g., Biben, 1986;Fagen, 1981;Meaney & Stewart, 1981;Smith et al, 1998).…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, even after one member of a pair has bitten the other, the recipient of the bite may begin to attack the partner's nape playfully after 1-2 min. Finally, Thor and Holloway (1985) have shown that playful attack (in what they refer to as play solicitation), decreased with age, even when the partners were treated with scopolamine, a cholinergic antagonist that suppresses playful behavior but not exploration and other activities. Thus, while scopolaminetreated rats do not initiate playful contact, or defend themselves against playful contact directed against them, they remain attractive targets for playful attack by undrugged rats.…”
Section: Age Changes In the Frequency Of Play Fightingmentioning
confidence: 99%